Motivation of disabled athletes for sport activities: validity and reliability of the Lithuanian version of the sport motivation scale - Sabaliauskas, Stanislav (Special Education, 2020)
The aim of the research was to evaluate the structural validity of the Lithuanian version of the Sports Motivation Scale in the context of the disability sport. This study included 66 athletes with hearing and visual impairment (45 men and 21 women). The average age of the research participants was 26.5 ± 11.7 years, they used to participate in sport activity for  10.1 ± 7.6 years. Athletes who participated in the research were representatives of goalball, tennis, athletics, swimming, basketball and other sports. 39 athletes were prize winners in World and European championships. The participants of the research completed the questionnaire based on the Sports Motivation Scale (SMS) already adapted in Lithuania. Data were processed using Jamovi program. SMS psychometric parameters demonstrated good internal scale compatibility. In the confirmatory factor analysis, a 4-factor model suitable for data analysis (CFI – 0.881; TLI - 0.863; RMSEA - 0.0710; χ2 / df 1.439) was identified which comprised 20 SMS items. The structure of the model consisted of factors that characterize athletes' intrinsic motivation – “to discover” (1), intrinsic motivation – “to feel self-improvement” (2), extrinsic motivation – “need for social dependency” (3) and “amotivation” (4).
Keywords: disability sport; confirmatory factor analysis; motivation for sport activities; motivation to discover; motivation to feel improvement